Semaphorin7A: branching beyond axonal guidance and into immunity - Garcia-Areas, Ramon (2013)
Semaphorins are a family of proteins that were originally described for their role in axonal guidance. Studies now show that semaphorins encompass many physiological functions outside of the nervous system, including immune responses. Semaphorin7A (SEMA7A) belongs to the “immune” semaphorin group and has been shown to play a crucial role in regulating immune responses. In this review, we discuss the structure and function of SEMA7A as well as its role of SEMA7A in innate and adaptive immunity. We further describe SEMA7A’s involvement in inflammatory disease and its emergent role in cancer.